PENGARUH TINGKAT PENDIDIKAN PEMAHAMAN AKUNTANSI DAN SKALA USAHA TERHADAP KUALITAS LAPORAN KEUANGAN PADA UMKM (Studi Pada UMKM di Sentra Tempe dan Keripik Tempe Sanan Kota Malang) - Lisa Mujianti; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
This study aims to determine the effect of the variable of education level, accounting understanding, and business scale on the quality of financial reports in Tempe and Sanan Tempe in Malang City. The method in this research is quantitative research. This study uses primary data. The scale used in the questionnaire is the likert scale and nominal. The population in this study is MSMEs located in the Sanan Region of Malang City, a total of 262 MSMEs. The sampling technique used is purposive sampling. So that obtained a sample of 57 respondents. The research data was processed by using multiple linear regression analysis with the help of SPSS version 25 for windows. The results of the research show : 1) education level has a significant effect on the quality of MSMEs financial reports. 2) understanding of accounting has a significant effect on the quality of MSMEs financial reports. 3) business scale has a significant effect on the quality of MSMEs financial reports.Keywords : Education Level, Accounting Understanding, and Business Scale